Instructional Leadership Role of Primary School Principals in Sri Lanka - Kumari, H.M.L. (International Journal of Latest Technology in Engineering, Management & Applied Science, 2023)
This study explores the instructional leadership (IL) role of primary school principals in Sri Lanka. The purpose of this study was to examine the practices of primary school principal’s role as instructional leader. The main research questions of the study were to find out what roles principal’s play as instructional leader in primary schools; Identify how primary school principal fulfill his/her instructional leadership role? And which activities do principals as instructional leaders engage in promoting the education of students and upgrading the pedagogy of teachers in primary schools. The multiple case study method was used in the current study. Accordingly, Semi-structured interview, focus group discussion, observation and document analyses were used as data collecting tools. As the study sample four principals, and four teachers were selected using purposive sampling for interviews. The study found that all principals in the sample experienced in implementing instructional leadership roles. Also, the study shows that the traditional role of principals as school leaders has been changed to instructional leaders. All the primary school principals mentioned that they implement innovative methodologies to overcome challenges that they face when implementing instructional leadership roles in their schools. Also the study found that a significsnt attention was paid on instructional supervision, giving feedback on instruction, provision of instructional materials and incentives for teaching and learning and protection of instructional time by primary schools principals as instructional leaders. The study further revealed that the opportunities available for primary school principals to acquire leadership training at an appropriate stage in their career are limited. It was further revelaed that Irrespective of education Zone the management of curriculum and instructional programs is a shared responsibility of principals and teachers in schools. However, principals should engage in all the roles related to instructional leadership in order to promote effective teaching and learning and thereby transform the school as an organisation into an environment where teachers and students reach their full potential. Therefore it is recommended that the primary school principals need to be trained in school management and leadership in order to be further competent as instructional leaders in primary schools in Sri Lanka.
Keywords: Instructional Leadership roles; primary Schools; Perception; Motivation